2008
DOI: 10.1002/adfm.200800507
|View full text |Cite
|
Sign up to set email alerts
|

Superoleophilic and Superhydrophobic Inverse Opals for Oil Sensors

Abstract: An inverse opal with both superoleophilic (oil contact angle (CA), 5.1° ± 1.2°) and superhydrophobic (water CA, 153.8° ± 1.2°) properties is fabricated using a phenolic resin (PR) as precursor and poly(styrene‐methyl methacrylate‐acrylic acid) (poly(St‐MMA‐AA)) colloidal crystals as templates. The stopband of the inverse opal can shift reversibly upon sorption of oils, whereby the peak position is a linear function of the refractive index of the adsorbed oil, e.g., a variation in refractive index of 0.02 will … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
111
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 116 publications
(113 citation statements)
references
References 60 publications
1
111
0
1
Order By: Relevance
“…In this case, hydrogen bonding is suppressed due to deprotonation of COOH to COO  . Additionally, many other works have also demonstrated the fabrication of surface with special wettability by combining its surface chemical composition and its roughness structure, for example, Li et al fabricated a superhydrophobic and superoleophilic phenolic resin [39]; Chen et al fabricated a superhydrophobic polyimide inverse opal [40].…”
Section: (1) Wettability Change Based On Surface Chemical Compositionmentioning
confidence: 98%
“…In this case, hydrogen bonding is suppressed due to deprotonation of COOH to COO  . Additionally, many other works have also demonstrated the fabrication of surface with special wettability by combining its surface chemical composition and its roughness structure, for example, Li et al fabricated a superhydrophobic and superoleophilic phenolic resin [39]; Chen et al fabricated a superhydrophobic polyimide inverse opal [40].…”
Section: (1) Wettability Change Based On Surface Chemical Compositionmentioning
confidence: 98%
“…An inverse opal with both superoleophilic and superhydrophobic properties is fabricated using a phenolic resin as precursor and colloidal crystals as templates. The stop band of the inverse opal can shift reversibly upon sorption of oils, whereby the peak position is a linear function of the refractive index of the adsorbed oil, e.g., a variation in the refractive index of 0.02 will result in a stop band shift of 26 nm [63]. Moreover, a colorful oil-sensitive carbon inverse opal was fabricated and the color shift upon absorption of the oil was reversible, and was easily visible to the naked eyes Figure 4 Schematic illustration of the opal/inverse opal films which are sensitive to different solutions.…”
Section: Pcs Optical Sensors Based On Refractive Indices Changesmentioning
confidence: 99%
“…Due to their ability to "manage" light over the range of its bandgap [81][82][83], inorganic semiconductor materials such as titania [84][85][86][87][88][89], silica [90][91][92][93], and zinc oxide [94] have all been made into inverse opals and studied extensively. In addition, other materials such as metals [42,80,[95][96][97][98][99][100] and organic materials [101][102][103][104][105] have also been fabricated into inverse opals and investigated.…”
Section: Inverse Opalsmentioning
confidence: 99%
“…Li et al demonstrated the use of inverse opals as oil sensors. They described the reversible shifting of the stop-band which varies as a linear function of the refractive index of the adsorbed oil [103]. Zhang et al described the development of a sensing material made of a crystalline 2D array of colloidal photonic crystal.…”
Section: Sensorsmentioning
confidence: 99%